Evaluation of multimedia resources for informatics education in Croatian elementary schools - Unić, Danijela; Boras, Damir; Mikelić Preradović, Nives (2012)
This paper aims to evaluate the existing interactive multimedia resources accompanying 4 different informatics education textbooks used by school teachers in Croatia and suggest a model of well-designed multimedia educational resource. Studies have shown that pupils using multimedia have higher achievement ratings, higher retention and acquire more information in less time and, therefore, we present a model that accommodates different learning styles (visual, aural, read/write, and kinesthetic), capture pupils' attention and augment their learning experience obeying all multimedia instructional design principles (the temporal contiguity, coherence and spatial contiguity principle) and reducing the possibility of the split-attention. Since these resources serve as a supplementary teaching and learning material to stimulate pupil's interest for learning, such evaluation should contribute to the teachers' and publisher's knowledge about affective multimedia design and enable them to understand the potential benefits and hinders of the multimedia design process.
ENG